CAE Tensile Analysis of Fiber Reinforced Polymers(FRP) - Perdum, Andrei-Ionut (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
This paper describe, how multiple CAE Analysis Simulations were evaluated to verify the influence of the filler in polymer matrix, by checking the differences in weight, density and maximum limit on tensile analysis(MPa) for each polymer composite (PA-MWCNT & PA-CF). Fiber reinforced polymer (FRP) composites were incorporated at different loadings of 10 wt. %., 20 wt. %., and 30 wt. %. Statistical Analysis results, reveals that high tensile limit has been achieved, when the addition of 30 wt. % of CF filler in the PA66 polymer matrix has been added. This paper explore the potential for a novel type of composite material incorporating carbon fiber (CF) and multi walled carbon nanotube (MWCNT). Recent work has shown that notable improvements in mechanical performance are achievable in reinforced polymers [1].